2012
DOI: 10.1021/jp309979p
|View full text |Cite
|
Sign up to set email alerts
|

Primary Radiation Defect Production in Polyethylene and Cellulose

Abstract: Irradiation effects in polyethylene and cellulose were examined using molecular dynamics simulations. The governing reactions in both materials were chain scissioning and generation of small hydrocarbon and peroxy radicals. Recombination of chain fragments and cross-linking between polymer chains were found to occur less frequently. Crystalline cellulose was found to be more resistant to radiation damage than crystalline polyethylene. Statistics on radical formation are presented and the dynamics of the format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…This supports the conclusion that preexisting damage is important for cross-linking and agrees well with our earlier results reported in Ref. 24, where single impact simulations with recoil energies up to 100 eV produced very little or no cross-links.…”
Section: B Cumulative Bombardmentsupporting
confidence: 93%
See 2 more Smart Citations
“…This supports the conclusion that preexisting damage is important for cross-linking and agrees well with our earlier results reported in Ref. 24, where single impact simulations with recoil energies up to 100 eV produced very little or no cross-links.…”
Section: B Cumulative Bombardmentsupporting
confidence: 93%
“…The simulation time was chosen based on our previous study, 24 where we found that the radical formation occurs during the first 1 ps after the recoil and most of the recombination during the next 3 ps, even with recoil energies as high as 100 eV. Damage affecting only H atoms was ignored, since it would be invisible in experiments such as TEM imaging.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes studies on the crystal structure of cellulose microfibrils (Matthews et al 2006;Wada et al 2011;Oehme et al 2015bOehme et al , 2018, and, as mentioned before, various aspects of the microfibril twist (Yui et al 2006;Matthews et al 2006;Yui and Hayashi 2007;Paavilainen et al 2011;Hadden et al 2013;Bu et al 2015;Conley et al 2016;Kannam et al 2017). Other studies have looked at the interactions of microfibrils with water (Yui et al 2006;Bergenstråhle et al 2008;Maurer et al 2013;Kulasinski et al 2015Kulasinski et al , 2017Lindh et al 2016;O'Neill et al 2017), their response to elevated temperatures (Matthews et al 2011(Matthews et al , 2012bZhang et al 2011); their mechanical properties (Paavilainen et al 2012;Saitoh et al 2013;Molnár et al 2018), aggregation and disintegration (Oehme et al 2015a;Paajanen et al 2016;Silveira et al 2016), chemical modification (Wada et al 2011;Paajanen et al 2016), enzymatic degradation (Beckham et al 2011;Orłowski et al 2015), and dissolution in ionic liquids (Gross et al 2011;Uto et al 2018); the pyrolytic degradation of cellulose (Zheng et al 2016;Paajanen and Vaari 2017); and radiation-induced defects (Polvi et al 2012;…”
Section: Computationalmentioning
confidence: 99%
“…38 Several of these processes were reported bombarded polyethylene. 45 Examining of the total number of broken bonds (if divided by two gives the number of fragments) in the different CNT/PE systems can assist in explaining the shape of the potential energy curve. Figure 10 reveals that a substantial number of fragments (mainly within the polyethylene) have been generated during the first 25 ps.…”
Section: Plotted Inmentioning
confidence: 66%